2005
DOI: 10.1292/jvms.67.1163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Computed Tomography for the Diagnosis of Feline Hepatic Lipidosis

Abstract: ABSTRACT. The usefulness of computed tomography (CT) for the diagnosis of feline hepatic lipidosis (FHL) was evaluated. Liver CT number was 54.7 ± 5.6 HU (mean ± SD) in 26 healthy cats. We fast 6 healthy cats for 72 hr to induced FHL experimentally and the cats were assessed by CT and serum biochemical analysis. Liver CT number of the six cats was 53.8 ± 3.0 HU before fasting, 46.8 ± 2.4 HU after fasting, and 50.2 ± 3.6 HU two weeks after restarted feeding. The decreased CT number was associated with the eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
1
15
1
Order By: Relevance
“…This technique provides valuable information, which complements those obtained by conventional imaging diagnosis methods such as radiographic and ultrasonographic exams (Rockall et al, 2003;Nakamura et al, 2005;. The greatest advantage of CT for veterinary medicine according to some authors is the speed in which the exam is performed, reducing movement artifacts and minimizing anesthetic time, being a non-invasive and safe method.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This technique provides valuable information, which complements those obtained by conventional imaging diagnosis methods such as radiographic and ultrasonographic exams (Rockall et al, 2003;Nakamura et al, 2005;. The greatest advantage of CT for veterinary medicine according to some authors is the speed in which the exam is performed, reducing movement artifacts and minimizing anesthetic time, being a non-invasive and safe method.…”
Section: Discussionmentioning
confidence: 98%
“…Computed tomography (CT) exams present a broad variety of indications for dogs and cats, becoming an important tool for the establishment of several diagnoses (Smallwood and George, 1993;Rockall et al, 2003;Nakamura et al, 2005;Ohlerth and Sharf, 2007;. The evaluation of abdominal organs' radiodensity is widely performed in human patients (Leander et al, 2000;Tsujimoto et al, 2006, Kodama et al, 2007 and can be employed with high precision and reproducibility in animals, helping in the diagnosis of alterations in several organs (Ohlerth andSharf, 2007, Teixeira et al, 2007;Costa et al, 2010).…”
mentioning
confidence: 99%
“…Based on the relatively low X‐ray attenuation of fat, CT has been used to detect visceral adipose tissue deposition in cats (range = − 156 to –106 HU), dogs (range = − 135 to − 105 HU), and meat‐producing animals . An experimental study in cats reported that measurement of the mean (SD) hepatic attenuation value in the liver using CT is an effective noninvasive procedure for the diagnosis of feline hepatic lipidosis . In 2013, Lam et al .…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomographic quantification of hepatic fat has been reported in one experimental study in cats . In that study, the mean hepatic attenuation in 26 normal cats was 54 HU (range 43.5–65.9 HU) .…”
Section: Introductionmentioning
confidence: 95%